Leadership Strategies to Improve Lecturer Performance at STAI Alhikmah Tebing Tinggi and STIT Batubara - Boyke Azwar; Amiruddin Siahaan; Rusydi Ananda (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This paper aims to analyze leadership strategies in improving lecturer performance at Private Islamic Higher Education Institutions (PTKIS), particularly at STAI Al-Hikmah Tebing Tinggi and STIT Batubara. The research focuses on lecturer performance, coordination patterns between PTKIS leaders and study programs, and leadership strategies to improve the implementation of the three pillars of higher education. The research method uses a qualitative approach with a multisite design in two research locations. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies. Data analysis was conducted descriptively and analytically through the stages of data reduction, data presentation, verification, and conclusion drawing, with validity testing through source and method triangulation. The results of the study show that the performance of lecturers at both institutions has been carried out in a planned and sustainable manner through the synergy of higher education leadership with study programs. Leadership coordination serves as a strategic mechanism in integrating academic policies with the implementation of the three pillars of higher education through planning, monitoring, evaluation, and professional development. Leadership strategies include the development of pedagogical competencies, strengthening a culture of research and scientific publication, science-based community service, creating a conducive academic environment, and a sustainable reward system. The discussion shows that collaborative leadership can improve the professionalism, motivation, and productivity of lecturers. However, challenges such as limited facilities, administrative burdens, and variations in lecturer competencies still need to be addressed, requiring visionary leadership and continuous guidance.